Pengaruh Media Daur Ulang Ampas Kelapa Terhadap Peningkatan Motorik Halus Dalam Pembelajaran Seni Mozaik Di Kb Permata Bunda - Istianah; Nur fajrie; Diah Kurniati (Bajang Institute, 2023)
The Effect of Recycled Coconut Dregs Media on Fine Motoric Improvement in Learning Mosaic Art at Kb Permata Bunda, The objectives to be achieved in this study are as follows: 1) To identify and describe fine motor skills in KB Permata Bunda Mayong Lor children, Mayong District, Jepara Regency. 2) To find out and describe the learning process by applying the demonstration method through a mosaic game for the children of KB Permata Bunda Mayong Lor, Mayong District, Jepara Regency. 3) To find out and prove the effectiveness of the application of the demonstration method through mosaic games in improving fine motor skills in KB Permata Bunda Mayong Lor children, Mayong District, Jepara Regency. This research is a study conducted in the classroom, because of that the researchers analyzed the data using the classroom action research (CAR) method. This classroom action research is designed to solve problems that are applied directly from within the class or in the learning process in class, namely at KB Permata Bunda Mayong Lor, Mayong District, Jepara Regency. The subjects of this study were children in KB Permata Bunda Mayong Lor, Mayong District, Jepara Regency, with a total of 12 children. The results of this study include: 1) The fine motor skills of students were successfully improved through the learning process by applying a mosaic game with natural coconut dregs as media for children aged 4-5 years at KB Permata Bunda Mayong Lor, Mayong District, Jepara Regency. 2) The application of the demonstration method through mosaic games in improving fine motor skills using natural coconut dregs as media for children aged 4-5 years at KB Permata Bunda Mayong Lor, Mayong District, Jepara Regency was effective. This is evidenced by the achievement of students' fine motor skills in pre-cycle was 35%, increased in cycle I was 50% and 60%, and increased again in cycle II with achievements of 74% and 85%. The indicator of children's success is 80% classically, in cycle II the child's achievement is 85% = 80% so it can be concluded that in cycle II this study was successful. 3) The teacher succeeded in carrying out the learning process by applying the demonstration method through a mosaic game with natural coconut dregs media for children aged 4-5 years at KB Permata Bunda Mayong Lor, Mayong District, Jepara Regency. This is evidenced by the final results of the teacher's performance which is 87%.